2021
DOI: 10.4103/ijri.ijri_483_20
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of chest HRCT findings in coronavirus disease pandemic (COVID-19)- An early experience

Abstract: Context: Corona virus disease (COVID-19) has spread in a rampant manner all over the World causing severe acute respiratory illness. Prompt recognition of disease is invaluable to ensure timely treatment, and rapid patient isolation is crucial for containment of this communicable disease. Aims: To evaluate the performance of high resolution CT (HRCT) in the diagnosis of COVID-19. To establish the role of HRCT in prognosis of affected patients and to assess severity of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…But the point to be noted is that for the RT-PCR positive cases or post-COVID, CT-scans are mandatory. These studies were also reported in previous literature [11] , [32] , [41] , [42] , but the main objective of this work is to understand the HRCT findings useful to apply image processing tools and for automated AI algorithms to classify and grade COVID-19 severity from the samples.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…But the point to be noted is that for the RT-PCR positive cases or post-COVID, CT-scans are mandatory. These studies were also reported in previous literature [11] , [32] , [41] , [42] , but the main objective of this work is to understand the HRCT findings useful to apply image processing tools and for automated AI algorithms to classify and grade COVID-19 severity from the samples.…”
Section: Discussionmentioning
confidence: 59%
“…The database statistics showed more infections in the age group of 30–60, with a higher rate of male patients. This demography may vary depending on location and populations, but there is a probability match of the statistics with those recorded in other parts of India [7] , [41] . Next, as per the HRCT findings on lung involvement, the pattern is similar in both genders with more effect on the upper-middle-lower lobes in the right and upper–lower in the left lung, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in India also reported similar findings, bilateral involvement was reported in 90.2% of the cases but with cases of unilateral involvement majority of them had right lung involvement (7.8%), while only 2% had unilateral left lung involvement. The same study also reported that the right upper lobe and right lower lobe were comparatively more involved when compared to the left side [ 18 ]. This perspective was also affirmed by a study conducted in China, which reported that the right lower lobe and upper lobes had higher CT severity scores than the left-sided respective lobes [ 19 ].…”
Section: Discussionmentioning
confidence: 93%
“…In a study conducted by Shah et al 28 of 216 patients it is noteworthy that 114 of the 216 patients (52.7%) had a normal HRCT scan. However, in our study only 1.1% of patients (3 patients) showed normal HRCT findings considering most of the patients were symptomatic and all the patients were admitted to our hospital requiring oxygen supplement.…”
Section: Discussionmentioning
confidence: 96%